Determinasi Kepuasan Nasabah BSI Mobile: Peran Kualitas Sistem, Informasi, dan Kemudahan Akses - Suhita, Sifa Uchtiat; Happy Sista Devy (Velocity: Journal of Sharia Finance and Banking, 2025)
This study aims to analyze the effect of system quality, information quality, and ease of access on customer satisfaction among users of the BSI Mobile application in Pekalongan Regency. This study uses a quantitative approach with purposive sampling techniques on 96 respondents. The data were analyzed using multiple linear regression with validity, reliability, and classical assumption tests. The results show that system quality has a significant negative effect on customer satisfaction, while information quality and ease of access have a significant positive effect. Simultaneously, all three variables have a significant effect on customer satisfaction. The finding regarding the negative effect of system quality is inconsistent with some previous studies, indicating that customers have high expectations of the performance of the BSI Mobile application. The implications of this study encourage improvements in system quality and user experience through system updates and digital education for customers.